Covid-19 in Brazil in 2020: impact on deaths from cancer and cardiovascular diseases - Beatriz Cordeiro Jardim; Arn Migowski; Flávia de Miranda Corrêa; Gulnar Azevedo e Silva (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To analyze the impact of the covid-19 pandemic on mortality from cancer and cardiovascular diseases (CVD) as underlying cause and comorbidity in Brazil and Brazilian regions in 2020. METHODS We used the 2019 and 2020 databases of the Mortality Information System (SIM) to analyze deaths occurring between March and December of each year that had cancer or CVD as the underlying cause or comorbidity. Deaths from covid-19 in 2020 were also analyzed. To estimate the Standardized Mortality Ratio (SMR) and the excess of deaths, 2019 data were considered as standard. RESULTS Between March and December 2020, there were 181,377 deaths from cancer and 291,375 deaths from cardiovascular diseases in Brazil, indicating reduction rates of 9.7% and 8.8%, respectively, compared to the same period of the previous year. The pattern was maintained in the five Brazilian regions, with lower variation for cancer (-8.4% in the South to -10.9% in the Midwest). For CVD, the variation was greater, from -2.2% in the North to -10.5 in the Southeast and South. In the same period of 2020, these diseases were classified as comorbidities in 18,133 deaths from cancer and 188,204 deaths from cardiovascular diseases, indicating a proportional excess compared to data from 2019, of 82.1% and 77.9%, respectively. This excess was most significant in the Northern Region, with a ratio of 2.5 between observed and expected deaths for the two conditions studied. CONCLUSIONS Excess deaths from cancer and CVD as comorbidities in 2020 may indicate that covid-19 had an important impact among patients with these conditions.